Authority control, a wasted tool in recovery systems - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2012)
The author argues that the list of authorities, as well as a professional tool, may represent an important role in information retrieval. The purpose of this paper is to offer an example to highlight how libraries and document databases have failed or have not yet reached their full potential in the knowledge society.
Keywords: Information retrieval; Authorities; Documentary languages; Disambiguation.